2017
DOI: 10.1002/chem.201700689
|View full text |Cite
|
Sign up to set email alerts
|

Borylative Radical Cyclizations of Benzo[3,4]cyclodec‐3‐ene‐1,5‐diynes and N‐Heterocyclic Carbene‐Boranes

Abstract: Borylative radical cyclization of benzo[3,4]cyclodec-3-ene-1,5-diynes to provide 5-borylated 6,7,8,9-tetrahydrobenzo[a]azulenes has been developed. The experimental results suggest that the reaction proceeds by a radical chain mechanism, in which di-tert-butyl hyponitrite (TBHN) works as a good radical initiator to form boryl radicals from N-heterocyclic carbene-boranes (NHC-boranes). The present reaction is a rare model that illustrates addition of boryl radicals to alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 51 publications
0
32
0
2
Order By: Relevance
“…Elegant work from Fensterbank, Lacôte, Malacria, and Curran has shown that N‐heterocyclic carbene (NHC)–boryl radicals can be generated by hydrogen atom abstraction from NHC−BH 3 complexes, which are powerful intermediates useful in building a wide range of value‐added boron compounds. For instance, Wang has developed radical borylation/cyclization cascade of 1,6‐enynes with NHC−BH 3 , and Curran and Taniguchi reported the Sato–Myers cyclization triggered by NHC–boryl radicals . Consistent with our continuing interest in development of atom‐economic and redox‐neutral transformations through hydrogen atom transfer (HAT)‐based photocatalysis, we envisioned that a photo‐mediated catalytic HAT process with NHC−BH 3 might deliver the boryl radical in a mild pathway, which could react with polyfluoroarenes and alkenes to introduce synthetically valuable fluorinated organic boranes (Scheme c).…”
Section: Introductionmentioning
confidence: 88%
“…Elegant work from Fensterbank, Lacôte, Malacria, and Curran has shown that N‐heterocyclic carbene (NHC)–boryl radicals can be generated by hydrogen atom abstraction from NHC−BH 3 complexes, which are powerful intermediates useful in building a wide range of value‐added boron compounds. For instance, Wang has developed radical borylation/cyclization cascade of 1,6‐enynes with NHC−BH 3 , and Curran and Taniguchi reported the Sato–Myers cyclization triggered by NHC–boryl radicals . Consistent with our continuing interest in development of atom‐economic and redox‐neutral transformations through hydrogen atom transfer (HAT)‐based photocatalysis, we envisioned that a photo‐mediated catalytic HAT process with NHC−BH 3 might deliver the boryl radical in a mild pathway, which could react with polyfluoroarenes and alkenes to introduce synthetically valuable fluorinated organic boranes (Scheme c).…”
Section: Introductionmentioning
confidence: 88%
“…Thereaction of the 10membered diyne 13 a with NHC-borane 17 (5 equiv) in the presence of di-tert-butyl hyponitrite (0.4 equiv) at 100 8 8Cd id not provide aborepin but instead gave 7,8,9tetrahydrobenzo[a]azulene 18 in 59 %y ield. [15] This product forms by an interrupted single hydroboration reaction, wherein the interrupting reaction is the transannular cyclization of the initial alkenyl radical.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Recently, we disclosed radical borylation/cyclization reactions of strained cyclic diynes with NHC‐boranes . Likewise, Wang and co‐workers reported radical borylation/cyclization reactions of enynes with NHC‐boranes and thiols as polarity‐reversal reagents .…”
Section: Figurementioning
confidence: 98%